2011
DOI: 10.15288/jsad.2011.72.259
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood, Alcohol Intake, and Drinking Contexts: Occasio Furem Facit

Abstract: ABSTRACT. Objective: The aim of this study was to assess whether the effect of parenthood on alcohol intake varies according to the context in which the drinking act occurs. Method: The data were drawn from the Canadian Addiction Survey, a national telephone survey conducted in 2004. The analytical sample included 1,079 drinking occasions nested in 498 female drinkers and 926 drinking occasions nested in 403 male drinkers between 18 and 55 years of age. A multilevel linear statistical model was used to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…Over several studies, a group of researchers has shown that drinking occasions are not invariant among individuals, regardless of individual characteristics, personality or predispositions, and that a great deal of the variability in alcohol intake is the product of contextual influences Kairouz & Greenfield, 2007;Paradis, 2011;Paradis, Demers, Nadeau, & Picard, 2011). These authors argue that social actors who find themselves in a specific context adjust their behavior to what is customary in that context rather than operate in accordance with norms connected to their individual profile.…”
Section: Introductionmentioning
confidence: 99%
“…Over several studies, a group of researchers has shown that drinking occasions are not invariant among individuals, regardless of individual characteristics, personality or predispositions, and that a great deal of the variability in alcohol intake is the product of contextual influences Kairouz & Greenfield, 2007;Paradis, 2011;Paradis, Demers, Nadeau, & Picard, 2011). These authors argue that social actors who find themselves in a specific context adjust their behavior to what is customary in that context rather than operate in accordance with norms connected to their individual profile.…”
Section: Introductionmentioning
confidence: 99%
“…1 This appears to shape the social norms regarding how a person may drink alcohol 2 as well as his or her opportunities to drink. 3 Numerous studies have shown that women drink smaller quantities, drink less often, and get intoxicated on fewer occasions. [4][5][6] While the hypothesis of a convergence between drinking patterns of men and women has been debated over time, this hypothesis has found limited support.…”
mentioning
confidence: 99%
“…4,7,8 In another way, gender differences in drinking go beyond drinking patterns. Men and women differ with regards to drinking contexts 3 and drinking motives. 9 These drinking practice dimensions are intertwined.…”
mentioning
confidence: 99%
“…These declines may be related to drinking contexts. A recent study found that both mothers and fathers report less frequent heavy drinking than non-parents, and that drinking contexts have gender-specific mediating effects (Paradis, 2011). For example, both mothers and fathers had a lower ratio of drinking at bars than non-parents, which was in turn associated with lower frequency of heavy drinking.…”
Section: Gender Drinking Contexts and Physical Abusementioning
confidence: 99%
“…the location where drinking occurs or the type of drinking companion) and risk for physical abuse (Friesthler, 2011; Freisthler & Gruenewald, 2013). Furthermore, the focus on heavy drinking or alcohol use disorders in existing literature has also led to little understanding about relationships between physical abuse and lower levels of alcohol consumption, which are more common in the general population (SAMHSA, 2012) and among parents compared to non-parents (Paradis, 2011). More recent work has begun to disentangle the drinking context from the amount of alcohol consumed, finding that where a parent drinks is associated with physical abuse (Freisthler, 2011; Freisthler & Gruenewald, 2013).…”
mentioning
confidence: 99%